Non-Invasive Cell Tracking with Brighter and Red-Transferred Luciferase for Potential Application in Stem Cell Therapy. Issue 12 (December 2019) - Dou, Lei; Matz, Ethan L.; Gu, Xin; Shu, Fangpeng; Paxton, Jennifer; Song, Jinlin; Yoo, James; Atala, Anthony; Jackson, John; Zhang, Yuanyuan
This study investigated the safety of a novel cell-labeling technology with mKATE and Renilla reniformis luciferase (mKATE-renLUC) and assessed the efficacy on tracking implanted human placental stromal cells (PSC) in an erectile dysfunction (ED) animal model. Human PSC were labeled with mKATE-renLUC using a lentivirus. Cell viability, apoptosis, proliferation, migration, surface marker expression and differentiation potential of the labeled PSC were evaluated and compared with non-labeled PSC. The paracrine profile of labeled cells was examined using an angiogenesis protein array. The brightness and duration of labeled cells with different densities were evaluated. An ED rat model was established and labeled PSC were injected into cavernosal tissue of the penis. The migration and distribution of transplanted PSC were monitored using an IVIS imaging system in real time. Implanted PSC were identified in isolated tissues via detection of mKATE fluorescence. The cell viability, morphology, proliferation, migration, surface marker expression and differentiation potential of mKATE-renLUC-labeled PSC were similar to those of non-labeled cells in vitro (no statistical difference p >0.05). Similar expressions of trophic factors were found between labeled and non-labeled PSC. The migration and distribution of PSC expressing renLUC were tracked in vivo using IVIS imaging system. mKATE-positive PSC were detected in penile, kidney, prostate and hepatic tissues using histological methods. This labeling technology provides a safe and effective cell-tracking approach with a brighter fluorophore and codon-optimized luciferase.